Tindak Tutur Ekspresif dalam Film Pendek “Kembali Pulang” Karya Klamby - Mochamad Rifky Fadilah; Ghina Nailal Husna; Alya Khaerunisa; Rahmatul Fatimah; Muhammad Raffa Aqilla; Asep Purwo Yudi Utomo; Kodrat Eko Putro Setiawan; Muhajir Muhajir (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
In everyday communication, expressive speech acts play an important role in conveying the speaker's emotions, feelings and attitudes towards a situation. Film as a communication medium also utilizes expressive speech acts as a medium that builds character and conveys messages to the audience. One film that is interesting to study from the perspective of expressive speech acts is the short film